Hubungan Kemampuan Membaca Kritis Dengan Kemampuan Menulis Teks Eksposisi Siswa Kelas X SMAN 3 Solok Selatan - Yulia Gustriani; Afrini Rahmi; Rahayu Fitri (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
he purpose of this study was to describe the relationship between critical reading ability and the ability to write expository texts for class X students of SMA N 3 Solok Selatan. This type of research is quantitative research using correlational methods. The sampling technique for this research was purposive sampling technique. Sampling is done based on the class that has the lowest standard deviation. The research sample is one class, namely class X-2, totaling 32 people. Research instruments in the form of questionnaires and performance tests. The questionnaire was used to collect students' critical reading scores while the performance test was used to collect exposition text writing skills scores. Based on the research results, the following conclusions can be drawn: First, the critical reading ability of class X students of SMA Negeri 3 Solok Selatan obtained an average score of 75.84 in the range of 76-85% on a scale of 10, with a Good qualification (B). Second, the ability to write expository texts for class X students of SMA Negeri 3 Solok Selatan obtained an average score of 78.33 in the range of 76-85% on a scale of 10, with a Good qualification (B). Third, there is a significant relationship between vocabulary mastery and the ability to write exposition texts of class X students of SMA Negeri 3 Solok Selatan. This shows that critical reading skills affect students in writing expository texts. This can be seen from the test results which prove that tcount > from ttable, namely 4,86 > 1.70.